INVISIBLE BARRIERS: SOCIAL INEQUALITY AND ITS IMPACT ON THE TEACHING AND LEARNING PROCESS - khairani, Cut; Fuady, Fuady; Zahriyanti, Zahriyanti; Iqbal, Muhammad; Wati, Mutia (Universitas Labuhanbatu, 2025)
Purpose - This study aims to determine and analyze the role of teachers in overcoming social inequality for students at UPTD SD Negeri 1 Kuala. The background of this research stems from the existence of social inequality in the world of basic education that affects students' academic and social development, especially in rural areas.Methodology - This research used a qualitative approach. Data were collected through observation, interview and document analysis techniques at UPTD SD Negeri 1 Kuala. Informants in this study included principals and teachers, who were selected based on representativeness considerations. Data were analyzed using interactive qualitative analysis techniques, which include data collection, data reduction, data presentation, and conclusion drawing.Results - The results showed that teachers have an important role in overcoming social gaps by building personalized social interactions with students, conveying religious and character values, and conducting discussions about bullying. Teachers also design bullying prevention programs and provide physical and non-physical support to victims. In addition, teachers provide guidance so that students can adapt to their friends, and instill a sense of caring and kinship between students.Contribution - This study contributes to the development of inclusive education by highlighting the strategic role of teachers in creating a fairer and more equitable learning environment